Assessment of physical, psychological, social, and environmental health domains of quality of life in female students living in dormitories of Qom University of Medical Sciences - Elaheh Rahiminia; Hoorieh Rahiminia; Gholamreza Sharifirad (International Archives of Health Sciences, 2017)
Aims: Considering significant number of students, especially female students consisting young stratum of the society, there is the increased possibility of mental damages and the direct effect it can have on their quality of life (QOL). The present study aimed to investigate the QOL in female students living in dormitories of the University of Medical Sciences in Qom University of Medical Sciences. Materials and Methods: This study is a cross-sectional study conducted in 2016 on 300 students of the Qom University of Medical Sciences selected using quota sampling. Data gathering tool was the World Health Organization QOL-BREF questionnaire containing 26 items. Statistical data were analyzed using descriptive and inferential statistics of SPSS software. Results: In general, the mean score of students in the four domains of QOL was respectively related to physical health (14.42 ± 2.42), social health (13.30 ± 3.33), environmental health (13.11 ± 2.95), and psychological health (13 ± 2.81), and also, there was a significant relationship between QOL and age (P < 0.0001), discipline (P < 0.04), economic status (P < 0.0001), and interest in discipline (P < 0.001). Conclusion: This study showed that the lowest area of QOL was associated with psychological health; therefore, to increase the QOL in this dimension; the periodical evaluation of the mental health is recommended. Appropriate training to create psychological adjustment in student dormitories can also improve the QOL.